The use and effect of social capital in new venture creation: Solo entrepreneurs vs. new venture teams - Uwe Cantner; Michael Stützer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This paper examines the use of social capital in the venture creation process. We compare solo entrepreneurs (n=182) and new venture teams (n=274) from a random sample of start-ups in innovative industries and test social capital use and its effects on firm performance. Our results reveal that solo entrepreneurs and new venture teams do not differ in their degree of use of social capital. However, there are differences in the determinants of social capital use in both groups. We find that weak ties assist solo entrepreneurs and have positive significant effects on new venture performance. For team start-ups, we find no direct effect of social capital. However, further tests indicate for teams that human capital variety positively moderates the effect of social capital on performance.
Keywords: M13; L25; L26; D83; 330; Entrepreneurship; Nascent entrepreneurship; Social capital; Start-up teams; Entrepreneurial learning; Unternehmer; Innovation; Gruppenarbeit; Social Capital; Lernprozess; Deutschland